Feasibility and kinetic study of electrocoagulation with enhanced flocculation-flotation in removal of color from synthetic dye - Simbuluk, Rose Artika; Niza, Noorzalila Muhammad (Science, Engineering and Health Studies, 2023)
In electrocoagulation, the gas bubbles develop as bubble nuclei, grow in size, break off from the electrode surface and rise in the liquid. Unfortunately, over time, the gas bubbles tend to adhere and accumulate on the electrode surface, deactivate the parts of the electrode surface that reduce the mass transfer of ions. This paper aimed to investigate the feasibility of electrocoagulation with enhanced flocculation-flotation to remove color from synthetic dye. Vibration of plates was utilized in electrocoagulation treatment, with the variables studied including pH (pH 5 and pH 9), vibration intensity (1.5 – 3.5 Volts), current intensity (0.5 – 2.5 A) and operating time (15 – 60 min). From the results, the optimum color removal percentage was 74.76%, achieved at a pH of 9 with optimum vibration and current intensities of 2.5 V and 2.5 A, respectively. For the kinetic study, the rate obtained for the highest R² value was the first-order reaction with a rate constant of 0.0037 min⁻¹ at acidic pH and 0.0022 min⁻¹ at alkaline pH. The vibration of plates enhanced the rate of coagulant ions as well as bubbles dispersion during the treatment due to the oscillation of plates, which generated a stirring mechanism around the electrode plates.